PENGGUNAAN GAMIS BAGI JAMA’AH TABLIGH: Studi Living Hadis pada Jama’ah Tabligh di Masjid Jami’ Al-Ittihad Yogyakarta - Khikmatiar, Azkiya (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2019)
This paper describes the use of the robe for Tablighi Jama'ah in Masjid Jami 'Al-Ittihad Yogyakarta based on the hadith of the Prophet. They understand the act of using the robe is the sunna of the Prophet as well as their identity. While the theory used is the theory of social action initiated by Max Weber. According to him, every human behavior has a subjective meaning to the culprit and directed to others. The result of his research is that the social action in using the robe for Tablighi Jama'ah in Masid Jami 'Al-lttihad has several action models, namely value-oriented social action, purpose-oriented socializing actions, and traditional actions. The three action models have interrelated phases.